The Forming Age and the Evolution Process of the Brine Lithium Deposits in the Qaidam Basin Based on Geochronology and Mineral Composition - Ma, Zhe; Han, Fengqing; Chen, Tianyuan; Yi, Lei; Lu, Xiaohang; Chen, Fuhong; Liu, Xiaobao; Yuan, Wenhu (Frontiers in Earth Science, 2021)
Lithium ore deposits are divided into pegmatite and brine deposits. The Puna Plateau and the Qinghai–Tibetan Plateau (QTP) have the most abundant brine lithium deposits worldwide. Very few studies have investigated the chronology of brine lithium deposits. This work reports the Optically Stimulated Luminescence (OSL) dating measurements of typical brine lithium deposits in the QTP comprising the East Taijinaier salt lake, West Taijinaier lake, and Yiliping lake on the central Qaidam Basin. Combining the OSL dating results with previous studies and mineral composition obtained from X-ray diffraction analysis (XRD), this study summarizes the age and characteristics of the climatic environment during the formation of brine lithium deposits in the Qaidam Basin. The major results are: 1) The brine lithium deposits in the Qaidam Basin started to form since 40 ka. The brine lithium deposits in South America, formed during the middle Pleistocene and late Pleistocene, are older than the deposits in the Qaidam Basin. The lithium deposits of Tibet formed around 4 ka, are the youngest. 2) The climate in the East Taijinaier and the West Taijinaier lakes was extremely cold and dry during 27-4.5 ka, with only a brief period around 10 ka when humid conditions prevailed. After 4.5 ka, the environment was comparatively more humid in both the lakes. The Yiliping lake had a dry climate since 38.09 ka; 3) East Taijinaier lake, West Taijinaier lake, and Yiliping lake were situated in the same secondary basin during the Late Pleistocene. However, tectonic activity around 40 ka led to the evolution of the Yiliping lake into an independent basin. The East Taijinaier lake and the West Taijinaier lake partitioned around 27 ka, then deposited the lower salt layers until the Holocene. The substantial amount of detrital minerals brought by the Nalinggele river during the Holocene led to brief desalination of the East taijinaier lake. The upper salt layer had been deposited in the E.taijinaier and West taijinaier lakes during this period due to the extremely dry climate.